Desain Pondasi Konstruksi Sarang Laba-Laba Pada Proyek Mini Extraction Plant for Asphalt Buton - Nurhayati, Yeti; Farida, Ida (Jurnal Konstruksi, 2017)
Along with tecnologi’s developments in civil engineering with environmental conditions mind, human resources can make a new invention. For example, Kontruksi Sarang Laba-laba (KSLL) or can be interpreted “the spider web contruction”. KSLL is a raft foundation one of shallow foundation wich modified by continous flat concrete, and the bottom part given by rigidity of straigt rib and soil improvement system. The all of part become monolith contruction unity. For that reason, the author take KSLL as an essay with title “Alternative Design KSLL Mini Extraction Plant for Asphalt Button. In this essay the author will focus to find out value of bearing capacity, primary stress, soil settlement, and the reinforcement’s requirement from KSLL. The author use quantitative descriptive research method, by calculating the foundation design which is able to resist and spread the upper structure load. The result of KSLL’s allowable bearing capacity is 514,095 kN/m2 in a clay’s surface, and soil settlement is 2,34 cm. With quality of concrete (fc’) K-250 and 29385 kg’s load to obtain 140x140 mm column, 6 Ø 12 primary reinforcement, Ø10 – 130  shear reinforcement (ok), thats mean the KSLL is able to resist a shear load from the outside. The hight of settlement’s rib is 1100 mm with T beam design calculation  which have Mn = 2271568900 N.mm > Mu = 581000 N.mm, thats mean Ø Mn will able to resist Mu. The contruction rib is 1000 mm with T beam design calculation  which have Mn = 2031698900 N.mm > Mu = 616000 N.mm, thats mean Ø Mn will able to resist Mu. And from of both rib will produce 6 Ø 12 primary reinforcement, Ø10 – 250 secondary reinforcement, and Ø10 – 250 practical shear reinforcement.